The China study : the most comprehensive study of nutrition ever conducted and the startling implications for diet, weight loss and long-term health - Campbell, T. Colin, 1934-; Campbell, Thomas M., II (BenBella Books, Inc., 2016)
This work presents the results of a large study of diet and death rates from cancer in adults across China and Taiwan and explains the study's significance and what it reveals about the implications of poor nutrition. While revealing that proper nutrition can have a dramatic effect on reducing and reversing these ailments as well as obesity, this text calls into question the practices of many of the current dietary programs, such as the Atkins diet, that enjoy widespread popularity in the West. The impact of the politics of nutrition and the efforts of special interest groups on the creation and dissemination of public information on nutrition are also discussed.